EFFECTS OF PURPLE LEAF EXTRACT ON NEUTROPHILS AND MACROPHAGES IN TOOTH EXTRACTION WOUNDS - Atik Kurniawati; Zainul Cholid; Budi Yuwono; Nadie Fatimatuzzahro; Putri Fajrin Widyatami; Neriza Ayuni Sunaryo (Journal of Vocational Health Studies, 2026)
Background: Tooth extraction induces trauma to the tissue and triggers an inflammatory response as part of the wound healing process. The early inflammatory phase is characterized by the accumulation of neutrophils and macrophages at the wound site. A prolonged inflammatory phase can result in excessive tissue damage. The purple leaf (Graptophyllum pictum L.Griff) extract (PLE) has been suggested to possess anti-inflammatory properties. Purpose: This study aims to analyze the effect of PLE on the number of neutrophils and macrophages in tooth extraction wounds. Method: This study employed a laboratory experimental design using a Post-Test-Only Control Group Design. A total of 32 male Wistar rats were divided into four control groups receiving distilled water and four treatment groups receiving 10% PLE administered by nasogastric on days 1, 3, 5, and 7. Following euthanasia, tissue samples were processed and stained using Haematoxylin-eosin. Neutrophils and macrophages were observed and quantified. The data were tabulated and analyzed statistically. Result: There was a significant difference (p-value < 0.05) between the control group and the treatment group. The 10% PLE treatment group showed a lower mean number of neutrophils and a higher mean number of macrophages than the control group on days 1,3,5, and 7. Conclusion: PLE affects the number of neutrophils and macrophages in tooth extraction wounds.